Role of p16, Ki67 and CK17 in differentiating benign lesions, cervical intraepithelial neoplasia(CIN) and atypical immature squamous metaplasia(AIM) of uterine cervix - Dr. Shaila K Mitra; Dr. Rajiv K Misra; Dr. Bharti Varshney; Dr. Ankita Kumari; Divya Rai (Tropical Journal of Pathology and Microbiology, 2017)
Cervical intraepithelial neoplasia (CIN) is a premalignant lesion capable of progressing to cervical cancer. Despite the existing well-defined criteria, the histopathological diagnosis is subject to high rates of discordance among pathologists.Aim: To study the role of p16, Ki67 and CK17 in differentiating benign lesions, cervical intraepithelial lesions(CIN) and atypical immature squamous metaplasia (AIM)and to improve intra and interobserver reproducibility of diagnosis of cervical neoplasia.Material and Methods: In a cross sectional study, a total of 75 cervical biopsies including benign lesions (n=24), AIM (n=28), CIN (n=23) were studied and analyzed immunohistochemically using p16, Ki67 and CK17 immunomarkers. Data was evaluated using chi-square test.Results: p16 and Ki 67positivity were observed in 91.3% and 78.26% of CIN and 28.57% of AIM respectively. None of the benign lesions expressed p16 and Ki67while CK17 positivity was observed in 46.42% of CIN and 100% of AIM with 12.5% of benign lesions.Conclusion: The three biomarkers (p16, CK17 and Ki67) had a high degree of sensitivity and specificity and appear to be a useful and reliable diagnostic adjunct to improve the routine diagnosis and reduce interobserver variability in cervical biopsy specimens. Immunohistochemical markers such as p16 alone or with Ki67 represents important tool for the pathologists in distinguishing high grade cervical dysplasia from its benign mimics such as AIM and reactive inflammatory lesion thus avoiding overtreatment.